Sect as a Threat – Cultural Memory and the Image of Sects. (3rd April 2017) - Lužný, Dušan
ABSTRACT: The year 1989 represented a decisive turn for the countries of Central Europe. With the breakdown of Communist regime a society based on market economy, political liberalism, and freedom of belief was (re)established. In the Czech environment, harsh atheism, anti-religious propaganda, persecution of believers, and dissolution of religious life were all parts of the Communist ideology and practice. The 'Velvet Revolution' meant, among others, also the opening of possibilities for independent religious life. The rise of religious freedom was accompanied by genuine religious plurality and the incoming or founding of new religious communities. Immediately, criticism of these non-traditional groups appeared (the so-called anti-cult movement) labelling the new groups as sects and perceiving them as a threat. The movement saw its task in facing up to this threat. The aim of this paper is to analyse and compare anti-sectarian narratives in Communist and post-Communist eras. The text raises the question of whether there exist interpretative frameworks transferrable in time and across diverse political and social conditions.